2018
DOI: 10.4037/ccn2018254
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Surgical Site Infections Related to Abdominal Drains in the Intensive Care Unit

Abstract: Surgical site infections are significant contributors to health care-associated infections. Nursing interventions may help decrease the incidence of surgical site infections, particularly in regards to the management of postsurgical abdominal drains. This comprehensive guide, compiled from evidence-based practice literature, is intended for nurses to use to reduce surgical site infections secondary to postsurgical abdominal drains. This article focuses on drain management in intensive care unit patients, who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Hand hygiene is the best way to prevent surgical site infections. Nurses should perform hand hygiene before and after touching the patient, before and after contact with drainage, and before and after wearing gloves, in addition to frequently changing gloves to prevent pathogen transfer to other parts of the body [26]. Nurses must also adhere to a series of infection management guidelines, such as avoiding touching the inside of the suction bulb when opening or closing the drainage tube and cleaning the area with an alcohol swab after emptying the bag [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hand hygiene is the best way to prevent surgical site infections. Nurses should perform hand hygiene before and after touching the patient, before and after contact with drainage, and before and after wearing gloves, in addition to frequently changing gloves to prevent pathogen transfer to other parts of the body [26]. Nurses must also adhere to a series of infection management guidelines, such as avoiding touching the inside of the suction bulb when opening or closing the drainage tube and cleaning the area with an alcohol swab after emptying the bag [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses must also adhere to a series of infection management guidelines, such as avoiding touching the inside of the suction bulb when opening or closing the drainage tube and cleaning the area with an alcohol swab after emptying the bag [27]. To assess surgical site infection, nurses should monitor whether the tube-site skin and dressing are clean and dry [28]; whether there are changes in the amount, color, transparency, and odor of drained fluid [26]; and whether they wear appropriate personal protective equipment (PPE), including gloves, to protect themselves from sudden exposure to body fluids [6]. The drainage tube management protocol, which includes these infection control principles, is expected to serve as specific learning material for nursing students to assess surgical site infections and prevent the transmission of infections related to drainage tubes.…”
Section: Discussionmentioning
confidence: 99%
“…There are a wide variety of drains available. They can be categorised as open or closed, and active or passive (Orth 2018). Open drains flow directly onto gauze pads or into a stoma bag, whereas closed drains have tubes that are connected to a bag or bottle.…”
Section: Use Of Drainsmentioning
confidence: 99%
“…As illustrated in this case study, ad hoc drain assessments can lead to inconsistent approaches, increase psychological distress and cause patient harm(Findik et al 2013, Liddle 2013, Woodrow 2013). Jim's care demonstrates that inadequate drain assessments and variable, uncoordinated care has potential iatrogenic consequences such as placing patients at risk of developing undiagnosed surgical site infections and the related danger of sepsis Orth (2018). identified that drains, particularly abdominal drains, generate ideal conditions for surgical site infections without appropriate management, which can lead to the development of sepsis(Khatoon et al 2015).…”
mentioning
confidence: 99%
“…S. aureus is a bacterium that resides on the skin and in the nares. The bacterium may be part of a patient's normal flora, can be acquired during the hospital stay, and is a potentially multidrug-resistant organism (Orth, 2018). It is estimated that MRSA is responsible Surgical-site infections (SSI) contribute to increased hospital length of stay, readmission rates, cost, and morbidity and mortality rates.…”
Section: Introductionmentioning
confidence: 99%